RBCs and DSGEs: The Computational Approach to Business Cycle Theory and Evidence - Oz̈er Karagedikli; Troy Matheson; Christie Smith; Shaun P. Vahey (Norges Bank, 2008)
Real Business Cycle (RBC) and Dynamic Stochastic General Equilibrium (DSGE) methods have become essential components of the macroeconomist's toolkit. This literature review stresses recently developed techniques for computation and inference, providing a supplement to the Romer (2006) textbook, which stresses theoretical issues. Many computational aspects are illustrated with reference to the simple divisible labour RBC model. Code and US data to replicate the computations are provided on the Internet, together with a number of appendices providing background details.
hdl:11250/2497768
Keywords: C11; C50; E30; 330; RBC; DSGE; Bayesian analysis; computation; simulation